Implementation of Christian Orthodox fasting improves plasma adiponectin concentrations compared with time-restricted eating in overweight premenopausal women. (17th February 2022) - Karras, Spyridon N.; Koufakis, Theocharis; Adamidou, Lilian; Dimakopoulos, Georgios; Karalazou, Paraskevi; Thisiadou, Katerina; Makedou, Kali; Zebekakis, Pantelis; Kotsa, Kalliopi
Abstract: The exact mechanisms mediating the metabolic effects of Orthodox fasting remain unclear. Plasma adiponectin, biochemical and anthropometrical data were evaluated in 55 Orthodox fasters (OF) and 42 time-restricted eating controls (all women, mean age 47.8 years) at three time points: baseline, end of the dietary intervention (7 weeks) and 5 weeks after participants returned to their typical dietary habits (12 weeks from baseline). In the OF group, there was an increase in adiponectin values at 12 weeks compared with baseline (9815.99 vs 8983.52 mg/ml, p = 0.02) and a reduction in body fat mass between baseline and 12 weeks (35.44 vs 32.17%, p = 0.004) and between 7 and 12 weeks (35.33 vs 32.17%, p = 0.003). In the same group, an inverse correlation between adiponectin and waist circumference values was observed over the entire study period. Our results provide novel evidence that Orthodox fasting has favourable metabolic effects related to improved adiponectin concentrations.